2018
DOI: 10.1159/000496390
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome <b><i>bcc-aa3</i></b> Oxidase Supercomplexes in the Aerobic Respiratory Chain of <b><i>Streptomyces coelicolor</i></b> A3(2)

Abstract: Streptomyces coelicolor A3(2), an obligately aerobic, oxidase-positive, and filamentous soil bacterium, lacks a soluble cytochrome c in its respiratory chain, having instead a membrane-associated diheme c-type cytochrome, QcrC. This necessitates complex formation to allow electron transfer between the cytochrome bcc and aa3 oxidase respiratory complexes. Combining genetic complementation studies with in-gel cytochrome oxidase activity staining, we demonstrate that the complete qcrCAB-ctaCDFE gene locus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…Only low levels of nitrate-reducing activity could be determined for the enzyme in mycelium. This would be consistent with the Nar1 enzyme being unable to accept electrons directly from menaquinol but would imply at the same time that the bcc-aa 3 complexes are not identical in spores and mycelium, a suggestion made in another recent study (9). While further studies will be required to determine what makes the Nar1 enzyme dependent on the bcc-aa 3 supercomplex in order to be able to reduce nitrate, it will also be important to determine whether the composition of the bcc-aa 3 supercomplex is different in these cellular compartments.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Only low levels of nitrate-reducing activity could be determined for the enzyme in mycelium. This would be consistent with the Nar1 enzyme being unable to accept electrons directly from menaquinol but would imply at the same time that the bcc-aa 3 complexes are not identical in spores and mycelium, a suggestion made in another recent study (9). While further studies will be required to determine what makes the Nar1 enzyme dependent on the bcc-aa 3 supercomplex in order to be able to reduce nitrate, it will also be important to determine whether the composition of the bcc-aa 3 supercomplex is different in these cellular compartments.…”
Section: Discussionsupporting
confidence: 69%
“…Manifestation of Nar1 activity requires the complete cytochrome bcc-aa 3 supercomplex. The results of a recent study have revealed that the bcc complex and the cytochrome aa 3 oxidase function as a supercomplex in S. coelicolor in both spores and mycelium during aerobic growth (9). The lack of Nar1 enzyme activity in spores of strain COE502A (Table 2), where only the CtaD subunit of the aa 3 oxidase is missing, suggested that the cytochrome bcc complex alone is insufficient to support Nar1 activity and that the complete bcc-aa 3 supercomplex is required to support Nar1dependent nitrate reduction in spores.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have resolved the structure of the bcc-aa 3 supercomplex from Mycobacterium smegmatis [8,9], revealing it to have a linear supramolecular organization comprising a complex III (bcc complex) dimer flanked at each end by an aa 3 oxidase (complex IV). A similar structure is also proposed for the Corynebacterium glutamicum supercomplex [10], and our own studies have revealed that a bcc-aa 3 supercomplex also exists in S. coelicolor [11]. However, the bcc-aa 3 in S. coelicolor appears to have a different composition in spores compared with mycelium [11].…”
Section: Introductionsupporting
confidence: 74%
“…A similar structure is also proposed for the Corynebacterium glutamicum supercomplex [10], and our own studies have revealed that a bcc-aa 3 supercomplex also exists in S. coelicolor [11]. However, the bcc-aa 3 in S. coelicolor appears to have a different composition in spores compared with mycelium [11]. It is currently unclear whether this compositional difference in S. coelicolor is perhaps due to altered physical stability, that is, disassembly, of the streptomycete supercomplex.…”
Section: Introductionsupporting
confidence: 66%